2021
DOI: 10.1186/s12889-021-11227-4
|View full text |Cite
|
Sign up to set email alerts
|

Association between income levels and prevalence of heat- and cold-related illnesses in Korean adults

Abstract: Background Given that low income worsens health outcomes, income differences may affect health disparities in weather-related illnesses. The aim of this study was to investigate the association between income levels and prevalence of heat- and cold-related illnesses among Korean adults. Methods The current study comprised 535,186 participants with all variables on income and health behaviors. Patients with temperature-related illnesses were defined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
2
0
1
Order By: Relevance
“…Single-country studies have also reported SES disparities in cold-related illnesses, e.g. for South Korea (Min et al, 2021). In terms of sensitivity to extreme temperatures, temperature vulnerability can be affected by pre-existing medical conditions and CVDs.…”
Section: Socio-demographic and Geographic Differentials In The Risk O...mentioning
confidence: 99%
“…Single-country studies have also reported SES disparities in cold-related illnesses, e.g. for South Korea (Min et al, 2021). In terms of sensitivity to extreme temperatures, temperature vulnerability can be affected by pre-existing medical conditions and CVDs.…”
Section: Socio-demographic and Geographic Differentials In The Risk O...mentioning
confidence: 99%
“…Previous studies have provided increasing evidence that vulnerable populations are the most affected by heat-related mortality and morbidity impacts [5,[18][19][20]. Due to the disproportionate effects of climate change on different vulnerabilities, such as the low-income, elderly, minorities, and those with chronic health conditions [21,22], previous studies have primarily focused on urban areas, overlooking the vulnerabilities and adaptations of rural communities.…”
Section: Introductionmentioning
confidence: 99%
“…A prevenção é possível mediante a identificação das áreas e indivíduos mais vulneráveis para a adoção de medidas de adaptação, políticas públicas de saúde e melhorias na infraestrutura urbana e habitacional. Estudos indicam(HONDULA et al, 2015;AHRENFELDT et al, 2020;MIN et al, 2021;VISSER;KUNST;FLEISCHMANN, 2022;BAKHTSIYARAVA et al, 2023) que o excesso de mortalidade acontece principalmente entre pessoas com 65 anos ou mais de idade e também em áreas com grandes desigualdades sociais e econômicas. As disparidades entre classes de rendimento exercem impactos tanto diretos quanto indiretos sobre a saúde da população.…”
unclassified